Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.4314/tjpr.v15i9.26
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and prevalence of metabolic syndrome among high-risk individuals attending internal medicine clinics across Jordan

Abstract: Purpose: To examine the prevalence and awareness of metabolic syndrome (MetS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Consistent with our outcomes, a study from Amman, Jordan, found no gender-based variation in the MetS frequency 22 . In the United States, MetS is more common in white males than females, while American blacks, Mexican Americans, Korean, Irani, Indian, and Kinmen women had a higher prevalence of MetS than men 23 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our outcomes, a study from Amman, Jordan, found no gender-based variation in the MetS frequency 22 . In the United States, MetS is more common in white males than females, while American blacks, Mexican Americans, Korean, Irani, Indian, and Kinmen women had a higher prevalence of MetS than men 23 .…”
Section: Discussionsupporting
confidence: 91%
“…Further, the occupation of women was mostly sedentary. Whereas, a study from Amman, Jordan, stated that there was no significant difference in the prevalence of MetS among sex [ 28 ]. In sharp contrast to the current study findings, MetS was higher among men than women from urban North-Central Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusive finding was obtained from the study conducted by Pokhrel R et al [13] in Pokhara, Nepal, where the prevalence among female patients was much higher. A study by Efaishat R et al [14] stated that there was no significant difference in the prevalence of metabolic syndrome among the sexes. In sharp contrast to the current study’s findings, metabolic syndrome was higher among men than women in a study conducted by Puppet F et al [15] in Urban North-Central Nigeria, where the prevalence of males was 74.5%.…”
Section: Discussionmentioning
confidence: 99%